Shabyar Ameliorates High Glucose Induced Retinal Pigment Epithelium Injury Through Suppressing Aldose Reductase and AMPK/mTOR/ULK1 Autophagy Pathway - Liu, Xiao Yan; Peng, Jun; He, Fei; Tursun, Xirali; Li, Shu Ping; Xin, Xue Lei; Aisa, Haji Akber (Frontiers in Pharmacology, 2022)
Shabyar (SBA)is a traditional medicine formula for relieving vision loss caused by factors including diabetic retinopathy (DR) in clinics. However, the mechanism of SBA's protective effect on retina has not been investigated. The present study aimed to investigate whether its protective effect was related to the inhibition of aldose reductase (AR) activity and autophagy-mediated retinal pigment epithelial cell injury or not. Human retinal pigment epithelial cells (ARPE-19) induced by high glucose was used as an in vitro model, with Epalrestat (EPL, AR inhibitor) and Difrarel (DFR, DR therapeutic drug) as positive controls. The results showed that SBA reduced metabolic disorders induced by AR protein and sorbitol in cell models. Western blotting and Polyol pathway products assay showed that SBA reduced the level of AR protein, ROS, and sorbitol, increased the level of Na+-K+-ATPase and alleviated cell edema. Western blotting and DCFH-DA probe assay showed that SBA decreased pAMPK/AMPK and pULK1/ULK1 which associated with autophagy initiation, down-regulated Beclin-1, Atg3, Atg5, Atg7, LC3 II/I and Bax/Bcl2, and up-regulated pmTOR/mTOR, P62 and mitochondrial membrane potential (MMP), reduces intracellular autophagosomes. Real-Time PCR assay showed that SBA had no significant effect on mRNA expression of AR and mTOR. These data demonstrated that SBA treatment inhibits the autophagy of ARPE-19 through the AMPK/mTOR/ULK1 signaling pathway, and reduced early-stage apoptosis occurred by high glucose. These findings reveal the protective role and mechanism of SBA on retinal pigment epithelium, and provide experimental basis for the clinical application of SBA in the treatment of DR.